Analisis Perolehan Angka dalam Permainan Olahraga Sepaktakraw - Abdul Aziz Hakim, (Pelangi Ilmu, 2007)
ABSTRACT The purpose of this study is to find know about, how to get points in Sepaktakraw. Also, survey method used on this study with data obtained by check list observations as the instrument. Twenty eight regu that play within fourth teen game on Kejurda Jawa Timur 2006 became objects on this study. Each player in every regu that used what ever technique to get a point to win the game, observed by a person observer. Therefore, needed six persons of observer to observed a match. The results of this study shown that greatest number of percentage of point that obtained is sepakmula 27,57%, then kedeng smash by right apit 0,06% and left apit 4,38 %, rolling smash by right apit 10,54% and left apit 6,56%, by right apit 4,98% and left apit 3,14%.